A new species of Gryllotalpa mole cricket (Orthoptera: Gryllotalpidae: Gryllotalpinae) from Peninsular Malaysia - Tan, Ming Kai; Kamaruddin, Khairul Nizam (Zootaxa, 2016)
A new species of Gryllotalpa mole cricket (Orthoptera: Gryllotalpidae) is described from Bukit Larut, Perak, Peninsular Malaysia: Gryllotalpa permai sp. n. Acoustic analysis of the male calling songs were also provided for Gryllotalpa permai sp. n. and the morphologically similar Gryllotalpa fulvipes.